ENTEROBIASIS AND ITS RELATIONSHIP WITH ENURESIS AMONGONE OF ORPHANGE CARE CHILDREN IN BAGHDAD- IRAQ - AL-Qadhi, Ban; AL-Warid, Harith; AL-Qadhi, Menahel (Iraqi Journal of Science, 2024)
The prevalence of Enterobiasis and Enuresis were screened in this study, to evaluatethe possible relationship between each other, and to investigate age, gender relatedfactors in fifty one orphanage Iraqi children their age (3-12) years, before and afteralbendazole treatment. The results showed that Enterobius vermicularis is one of themost frequent parasites in orphanages, the overall infection rate (84.31%) was reportedin this study, and gender is less related with the prevalence of enterobiasis , the infectionrate in males(55.81%) was higher than females(44.18%) , although there was nosignificant relation (p0.05) between gender and infection rate of enterobiasis , while asignificant relationshp between enterobiasis and nocturnal enuresis were investigated(p0.05) , the percentage of children who had pinworm infection and enuresis was58.82% before treatment, while the percentage after treatment with Albendazole was11.76%. Questionnaire interviews were used to determine which of the children sufferedfrom some clinical symptoms gathered with enuresis.